A strategy for alleviating aviation shortages through the recruitment of women. (2016) - Opengart, Rose; Ison, David
This mixed-methods study investigated the experiences of female pilots. Commercial and corporate female pilots answered the following question, 'How can we recruit and retain more women pilots'? 61 surveys and 10 interviews were completed by people of different gender, age, and nationality. Two qualitative software packages were utilised for analysis. The results of this study indicate that US and Canadian female pilots face significant barriers to their career paths, confirming studies in the UK and Australia. Themes found include: need for supportive other, need for confident, strong personality, parental and familial encouragement, desire for challenge and excitement, need for awareness and role models, and systems-level problems. Conclusions and implications include: remove barriers and impediments, lower cost for entry and increase initial salaries, increase visibility and outreach, address retention in addition to recruitment, leadership and organisational support, importance of culture and support, and provide more flexibility in scheduling and structure.